1999
DOI: 10.1046/j.1365-2044.1999.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre‐emptive acupuncture treatment on analgesic requirements after day‐case knee arthroscopy

Abstract: SummaryThe role of acupuncture analgesia in the management of postoperative pain is yet to be clearly evaluated. We conducted a prospective, double-blind, randomised controlled study to evaluate the effect of acupuncture pretreatment on the analgesic requirement after knee arthroscopy. Forty-two patients presenting for unilateral knee arthroscopy were randomly allocated to receive a standard anaesthetic with or without acupuncture (given after the induction of anaesthesia). Visual analogue pain scores, time to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 0 publications
2
12
0
2
Order By: Relevance
“…There were no significant differences between the acupuncture and control groups. 30 The lack of significant difference between groups I and II (the two timings of EA) suggests that the use of intraoperative EA adds nothing to the perioperative stimulation, confirming the findings of others that acupuncture is ineffective if given during anaesthesia.…”
supporting
confidence: 60%
“…There were no significant differences between the acupuncture and control groups. 30 The lack of significant difference between groups I and II (the two timings of EA) suggests that the use of intraoperative EA adds nothing to the perioperative stimulation, confirming the findings of others that acupuncture is ineffective if given during anaesthesia.…”
supporting
confidence: 60%
“…To our knowledge five prospective, controlled studies on acupuncture for postoperative pain relief are reported in such detail that reproduction would be possible (1)(2)(3)(4)(5). An analgesic effect of acupuncture was found in three of these studies (1, 2, 5) but not in the other two (3,4).…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge five prospective, controlled studies on acupuncture for postoperative pain relief are reported in such detail that reproduction would be possible (1)(2)(3)(4)(5). An analgesic effect of acupuncture was found in three of these studies (1,2,5) but not in the other two (3,4). However, the design of one study (1) reporting reduced use of analgesics in acupuncture patients during only the first two postoperative hours is dubious, since the control patients seem to have had an approximately half-hour shorter period of anaesthesia than the acupuncture patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10;11 In knee arthroscopy acupuncture could not reduce postoperative pain. 12 In contrast recent studies showed decrease of postoperative opioid consumption by TENS or intradermal needles. 13;14 Postoperative Nausea and Vomiting (PONV) Most randomised controlled trials (RCT) of acupuncture for the prevention of PONV exist for stimulation of PC6.…”
Section: Postoperative Pain Managementmentioning
confidence: 90%